2021
DOI: 10.2486/indhealth.2021-0162
|View full text |Cite
|
Sign up to set email alerts
|

Association between preventive measures against workplace infection and preventive behavior against personal infection

Abstract: To prevent the spread of infection, it is necessary for each individual to adopt infection prevention behavior. We investigated the effect of infection control measures implemented in the workplace on personal infection prevention behavior. We conducted a self-administered questionnaire survey through the Internet from December 22 to 25, 2020, during which period coronavirus disease 2019 (COVID-19) was spreading. Among respondents aged 20 to 65 years (n=27,036), 21,915 workers were included in the analysis. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Married people are likely aware of their domestic situation as an infection route [40,41] and thus pay more attention to the possible ways in which their family members may become infected, in addition to their own infection risk, which may have contributed to their self-restraint. The self-restraint behaviors of the highly educated and the high-income earners may be explained by their generally high health literacy [43,44], which conceivably stems from their ability and desire to actively collect and select valid information, resulting in increased risk perception and the adoption of behaviors that protect them from COVID-19 [34]. For many people whose jobs involve mainly desk work, they are often able to work from home, which in itself is part of the recommended infection control measures and may therefore raise these workers’ risk perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Married people are likely aware of their domestic situation as an infection route [40,41] and thus pay more attention to the possible ways in which their family members may become infected, in addition to their own infection risk, which may have contributed to their self-restraint. The self-restraint behaviors of the highly educated and the high-income earners may be explained by their generally high health literacy [43,44], which conceivably stems from their ability and desire to actively collect and select valid information, resulting in increased risk perception and the adoption of behaviors that protect them from COVID-19 [34]. For many people whose jobs involve mainly desk work, they are often able to work from home, which in itself is part of the recommended infection control measures and may therefore raise these workers’ risk perception.…”
Section: Discussionmentioning
confidence: 99%
“…Even in workplaces where people engage in interpersonal communication, measures against infection have been strengthened to avoid infecting customers as well as employees. One report showed that infection control measures in the workplace cause individuals to strengthen their own protective measures [44]; thus, such workplace measures may naturally raise an individual worker’s risk perception. Finally, people who have an underlying disease are at an increased risk of becoming more severely ill if they contract COVID-19 [39], information that is, at least in Japan, repeatedly disseminated by the government and experts, which may have raised the perception of risk in this group and led to the reported self-restraint.…”
Section: Discussionmentioning
confidence: 99%
“…Infection control in the workplace, which is where workers spend most of their time and therefore a major place of human contact, has been reported to affect not only infection prevention but also workers' mental well-being and performance. [9][10][11][12] COVID-19 measures taken by Japanese employees include refraining from going to work when sick, measuring their body temperature, disinfecting the workplace, and teleworking. However, the extent to which the various control measures are implemented varies with the size of the company, the type of work, and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, enhanced infection control measures in the workplace were also reported to be associated with individual preventive behaviors such as hand washing. 10 We hypothesized that infection control efforts in the workplace also influence people's interactions, including romantic activities, during the COVID-19 pandemic. It is conceivable that during the pandemic, seeking a new romantic partner is influenced by one's perception of infection risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation